Dystrophic epidermolysis bullosa associated with non-syndromic hypodontia - Sonali Sharma; Sumit Bedi (Wolters Kluwer Medknow Publications, 2013)
Epidermolysis bullosa (EB) is a genetic disease associated with fragility and bullous lesions of the skin and mucous membranes. There are various patterns of inheritance and histopathology. The disease is associated with systemic and oral manifestations, among which may be dental decay necessitating oral rehabilitation. The aim of this article is to present the course of the condition in a child with dystrophic EB and also to report an association between EB, hypodontia, and supernumerary teeth which has not been reported earlier in literature.